2013
DOI: 10.1371/journal.pone.0079214
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Green Tea and Rock Tea Consumption with Risk of Impaired Fasting Glucose and Impaired Glucose Tolerance in Chinese Men and Women

Abstract: ObjectiveTo explore the associations of green tea and rock tea consumption with risk of impaired fasting glucose (IFG) and impaired glucose tolerance (IGT).MethodsA multistage, stratified, cluster, random-sampling method was used to select a representative sample from Fujian Province in China. In total, 4808 subjects without cardiovascular disease, hypertension, cancer, or pancreatic, liver, kidney, or gastrointestinal diseases were enrolled in the study. A standard questionnaire was used to gather data on tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
8
1
2
Order By: Relevance
“…Green tea consumption was associated with a lower risk of impaired fasting glucose (IFG), while oolong tea consumption was associated with a lower risk of impaired glucose tolerance (IGT). A U-shaped association was observed, subjects who consumed 16–30 cups of green and oolong tea per week had the lowest ORs for IFG and IGT, respectively [ 22 ], suggesting that green tea and oolong tea showed antidiabetic effects through different mechanisms. The chemical composition of teas varies with the degree of fermentation.…”
Section: Epidemiologic Evidencesmentioning
confidence: 99%
“…Green tea consumption was associated with a lower risk of impaired fasting glucose (IFG), while oolong tea consumption was associated with a lower risk of impaired glucose tolerance (IGT). A U-shaped association was observed, subjects who consumed 16–30 cups of green and oolong tea per week had the lowest ORs for IFG and IGT, respectively [ 22 ], suggesting that green tea and oolong tea showed antidiabetic effects through different mechanisms. The chemical composition of teas varies with the degree of fermentation.…”
Section: Epidemiologic Evidencesmentioning
confidence: 99%
“…11 In recent years, some studies have found that drinking tea may lower the risk of developing T2DM by affecting glucose digestion, glucose uptake, and insulin activity. 12,13 A meta-analysis of 9 cohort studies reported a 20% lower risk of T2DM for people who drank ≥4 cups of tea per day. 14 However, other studies found no association between tea consumption and diabetes risk.…”
mentioning
confidence: 99%
“…The results of a case-control study conducted in the People's Republic of China with 4,800 subjects indicated that the consumption of green tea possibly protects against the development of type 2 diabetes, particularly in those who drink 16-30 cups/wk. 40 A meta-analysis performed on 12 eligible studies found that daily tea consumption ($3 cups/d) was associated with a lower risk of type 2 diabetes, with a relative risk of 0.84 compared with that of the lowest consumption and non-tea-drinking groups. 41 A study on beverage consumption in 25,639 adults in the UK found that the consumption of sugar-sweetened beverages was associated with high risk of type 2 diabetes, independent of adiposity.…”
Section: 500mentioning
confidence: 99%